The Effect of Emotional Intelligence and Spiritual Intelligence on Lecturer Work Performance - Nurzaman, Lisye; Amalia, Lia (Eligible : Journal of Social Sciences, 2022)
The purpose of this research is to observe the influence of emotional intelligence and spiritual intelligence on lecturer work performance and also to explore the moderation effect of lecturer certification on the correlation between emotional intelligence and spiritual intelligence towards the lecturer work performance. This research uses the quantitative approach by applying the survey method based on primary data. Data is collected from 306 respondents who are full-time lecturers in Pelita Harapan University, with 59 indicator questions under the category of emotional intelligence, spiritual intelligence and lecturer work performance. The sampling technique in this research is simple random sampling. The Analyzing instrument used Partial Least Squares Structural Equation Model (PLS - SEM). The result of the research reveals that emotional intelligence positively and significantly influences lecturer work performance, lecture certification does not give a positive influence in moderating between spiritual intelligence and lecturer work performance. This result of this research is beneficial for Higher Education in determining policies or descisions that will be taken in the management and the improvement of lecturer work performancer.